Siskeudes As A Village Governance Instrument: An Analysis Of Effectiveness And Implementation Challenges - Hayati, Tri; Bangun, Raihatunnisa; Tampubolon, Jason Nicholas Bonar Parulian; Muchsin, Muhammad Arsyad Hawari; Marpaung, Glen Hasian; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The Village Financial System (Siskeudes) was developed by BPKP and the Ministry of Home Affairs as a digital instrument to enhance transparency, accountability, and effectiveness in village financial management. This study aims to analyze the effectiveness of Siskeudes in supporting village financial governance and to identify the challenges encountered during its implementation. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations of Siskeudes usage processes, and document reviews, including the Village Budget (APBDes), accountability reports, and application-generated outputs. The research informants include the Village Head, Village Secretary, Finance Officer, Siskeudes operator, Village Consultative Body (BPD), and village facilitators in Suka Damai Village, Kuala Subdistrict, Langkat Regency. The findings indicate that Siskeudes is effective in improving administrative order, accelerating report preparation, minimizing potential irregularities, and strengthening public transparency and accountability. The application also facilitates audits through automatically structured and consistent transaction records. However, the effectiveness of implementation is hindered by limited human resource competencies, inadequate technological infrastructure, reliance on a single operator, suboptimal data synchronization, and updates to the system that are not always accompanied by improvements in village officials’ capacities. This study recommends strengthening human resource capacities, improving digital infrastructure, integrating data across institutions, and developing a system that is more adaptive to village needs. These findings affirm that Siskeudes is a strategic instrument for realizing modern and accountable village governance